5'-O-Methylphosphonate nucleic acids--new modified DNAs that increase the Escherichia coli RNase H cleavage rate of hybrid duplexes - Šipova, Hana; Špringer, Tomaš; Rejman, Dominik; Šimak, Ondřej; Petrová, Magdalena; Novák, Pavel; Rosenbergová, Šarka; Páv, Ondřej; Liboska, Radek; Barvík, Ivan; Štěpanek, Josef; Rosenberg, Ivan; et al. (Nucleic acids research, 2014)
Several oligothymidylates containing various ratios of phosphodiester and isopolar 5'-hydroxyphosphonate, 5'-O-methylphosphonate and 3'-O-methylphosphonate internucleotide linkages were examined with respect to their hybridization properties with oligoriboadenylates and their ability to induce RNA cleavage by ribonuclease H (RNase H). The results demonstrated that the increasing number of 5'-hydroxyphosphonate or 5'-O-methylphosphonate units in antisense oligonucleotides (AOs) significantly stabilizes the heteroduplexes, whereas 3'-O-methylphosphonate AOs cause strong destabilization of the heteroduplexes. Only the heteroduplexes with 5'-O-methylphosphonate units in the antisense strand exhibited a significant increase in Escherichia coli RNase H cleavage activity by up to 3-fold (depending on the ratio of phosphodiester and phosphonate linkages) in comparison with the natural heteroduplex. A similar increase in RNase H cleavage activity was also observed for heteroduplexes composed of miRNA191 and complementary AOs containing 5'-O-methylphosphonate units. We propose for this type of AOs, working via the RNase H mechanism, the abbreviation MEPNA (MEthylPhosphonate Nucleic Acid).
Keywords: ribonukleasa H; Oligonucleotides, Antisense; mikro RNA; RNA Cleavage; antisense oligonukleotidy; MicroRNAs; Organophosphonates; Escherichia coli; Ribonuclease H; organofosfonáty; štěpení RNA